The relationship of the annual pursuit grades with academic achievement in the ministerial exam for the primary stage (Journal of the College of Basic Education, 2022)
The research aimed to identify:1- The correlation between grades of annual pursuit and academic achievement in the ministerial exam for primary school students.2- Significance of differences in the relationship between grades of annual pursuit and academic achievement in the ministerial exam according to the gender variable (males, females).The research sample consisted of (400) four hundred male and female students from (10) ten schools of mixed primary schools in the Baquba district of the center, who were chosen randomly, and the degrees of the annual pursuit and the ministerial exam were obtained for students from the schools targeted by the current study using indirect observation Score lists, scan and review them, and then extract the relationships